Determinants price earnings ratio of services sector in Malaysia/ Nur Anis Haikal Ismail - Ismail, Nur Anis Haikal (2018)
This purpose of the research is to know what factors that determine the price earnings ratio of services sector that listed in Bursa Malaysia. The service sector is an important part of the economy which it is the primary driver of the economic. The activities in the services sector include retail, banks, hotels, real estate, education, health, social work, computer services, recreation, media, communications, electricity, gas and water supply. This research investigates the degree of correlation of the five determinants which are dividend payout ratio, return on equity, operating profit margin, debt to assets and corporate size while price earnings ratio as dependent variable. The data were obtained from secondary data which gathered from annual report of the companies. The study examines ten services companies listed in Bursa Malaysia over period of years from 2012-2017 annually. The study examines the determinants of price earnings ratio by using ordinary least square regression analysis. On the findings, there are three variables significant effect price earnings ratio which are dividend payout ratio, operating profit margin and company size proxy of total assets. While the other two variables are not significant effect price earnings ratio.